Pengembangan Sistem Informasi Inventori Berbasis Java Pada CV. Bagaskara Galih Perkasa Jepara - Kusumodestoni, R. Hadapiningradja; Widiastuti, Nur Aeni; Sucipto, Adi; Setiawan, Fendi (Teknik Elektro - Politeknik Negeri Semarang, 2018)
CV. Bagaskara Galih Perkasa Jepara is one of the companies engaged in furniture. Current inventory systems still have many shortcomings and weaknesses that cause the companys performance to be less than the maximum. There is inefficient data recording process because the same data recording is done several times because the form is available separately, and the absence of notification